Behaviour, synchrony and welfare of Pekin ducks in relation to water use - Waitt, C; Jones, T; Dawkins, M (2009)
The method of providing bathing water to commercially farmed ducks presents potential logistic, welfare and health issues. Welfare may be compromised if ducks do not have access to water in which they can at least dip their heads and spread water over their feathers. However maintaining hygiene and environmental standards is difficult with open water in which ducks can immerse themselves. Here we present evidence on the welfare implications of providing bathing water to ducks from baths, troughs, showers and nipples. We ask whether they allow ducks to exhibit the full range of bathing behaviours and examine synchrony of bathing behaviour. The total time ducks spend at the resource during a bathing bout was not different between the bath, trough and shower but was least at the nipple (563-818 s compared to 243 s, p = 0.004). Most elements of the bathing sequence were displayed at all resources, although some behaviours were redirected at the straw in the nipple group. On the whole, there was no difference between the duration and frequency of the bathing elements for ducks at the bath, trough and shower, which were longer and more frequent than at the nipples. There was however, more resting under the shower than with the bath (214 s compared to 47 s, p = 0.02), and more wing-rubbing at the trough than the bath (7 s compared to 1.5 s, p = 0.009). There was no effect of resource on the time spent head rolling or the frequency of scratching and body shaking. Additionally, the sequence of behavioural elements within the bathing bout was more variable in the bath and under the shower than at the nipple (4.1 compared to 3.6, p = 0.02). Finally, ducks at the nipples spent proportionally more time at the resource singly (61.2%, p = 0.044). Whereas ducks at the bath, trough and shower used the resources more socially, spending proportionally more time at the resource when two or more ducks were there simultaneously (52.1-67.6% for the three resources). We conclude that (i) the expression of bathing behaviour, as measured by duration, frequency and sequence of bathing elements, was similar in showers and troughs to baths, but different in nipples, and (ii) bathing water resources need to allow for a degree of social bathing, but need not cater for all ducks simultaneously. © 2009 Elsevier B.V. All rights reserved.